Does Long-Term Sport Practice Facilitate the Development of Idiopathic Bradycardia Requiring Early Pacemaker Implantation During the Course of Life? - Sergei Bondarev; Leonardo Brotto; Francesca Graziano; Alberto Cipriani; Domenico Corrado; Alessandro Zorzi (Journal of Cardiovascular Development and Disease)
Background: Sinus bradycardia and first-/second-degree atrioventricular (AV) block in athletes are traditionally considered secondary to increased vagal tone and therefore reversible. However, recent studies have suggested that they may persist even after the cessation of physical activity, and combined with the effects of aging, lead to the earlier onset of clinically significant bradyarrhythmias. Methods: We evaluated the correlation between lifetime sport practice and the age of the onset of premature (≤70 years old) idiopathic sinoatrial node or AV node dysfunction requiring pacemaker (PM) implantation. Results: Of the 1316 patients followed up with at our PM clinic in 2024, we included 79 (6%) who received a PM when they were ≤70 years old for bradyarrhythmias in the absence of secondary causes. Nineteen (24%) had engaged in at least 6 h of sports/week for ≥20 years and were classified as former athletes. For comparison, former athletes who received a PM for idiopathic bradycardia at >70 years old were 6% (p < 0.001). In the group ≤70 years old, the average age of PM implantation was 62.8 years in non-athletes versus 57.9 years in former athletes (p = 0.03). The main reason for PM implantation was AV block in both subgroups. Among former athletes, the correlation between the lifetime volume of sports activity and the age of PM implantation reached borderline statistical significance (p = 0.08). Echocardiography at the time of implant did not reveal significant differences between former athletes and non-athletes. Conclusions: In a cohort of patients who received a PM for bradyarrhythmia before the age of 70 years old in the absence of secondary causes, former athletes were implanted on average ≈5 years before non-athletes. This may suggest a contributing role of cumulative sports activity volume in the development of idiopathic sinus/AV node dysfunction.